Inter-Organisational Collaboration Networks in The Introduction Phase of Generative AI - Isada, Fumihiko (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2025)
The goal: This research is a preliminary report that analyses the inter-organisational collaboration networks related to generative AI (Artificial Intelligence), which has spread rapidly in recent years, and empirically clarifies the key players and their relationships in the business ecosystem during the introduction phase of the technology lifecycle. The methodology: Information on the collaborative relationships between organisations in the six months following the launch of Chat GPT4 in March 2023, which triggered the rapid expansion of the actual use of generative AI in companies, etc., was extracted from more than 100 major newspaper articles and press releases worldwide, and analysed using the method of social network analysis. The conclusion: The development and utilisation of generative AI is increasingly forming a business ecosystem with very diverse inter-organisational collaborations on applications and system devices, and each organisation is strategically positioning itself within the business ecosystem. The empirical analysis of the structure of the inter-organisational collaboration network has allowed an exploratory identification of various distinctive organisations in the business ecosystem.